Analysis of the Administrative Process of MSME Business Contracts in the Rest Area at PT. Jasamarga Related Business - Idzni Hadziyah; Marliyah Marliyah (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
Contract making is an important part of running a business relationship, with a business contract making it the most important thing for business actors before they cooperate. This study aims to determine how the administrative process of MSME business contracts in the Rest Area area at PT. Jasamarga Related Business. Research uses qualitative or descriptive analysis methods, namely research that is intended to determine the circumstances, conditions, events, activities and other matters, or qualitative methods are methodologies using content analysis, which in writing requires steps to be passed to achieve the goals and objectives. complete and objective data and have certain methods and methods according to the problems to be discussed. The types of research are field studies and literature studies. The results of this research can be concluded that with the existence of a business contract process or agreement at the beginning before starting a business cooperation between the tenant and PT. Jasamarga Related Business Belmera Branch is very influential because it shows that in the lease activity contract it can be applied as a bridge for the tenant and PT. Jasamarga Related Business, with contract agreements as evidence and media to build cooperation, and contracts in the form of written agreements that can provide legal certainty for the parties involved in the cooperation. With the existence of a contract that functions as a binder for the parties involved in the cooperation, then with this leasing activity can run well. In providing the terms of the business contract, the giver and the one who is given the conditions there must also be no coercion, must be with a will from within themselves to accept whatever conditions are given.